Health state perception of people close to retirement age: Relationship with lifestyle habits and subjects’ characteristics - Diana Monge-Martín; Fernando Caballero-Martínez; Maria João Forjaz; Manuel J. Castillo; Carmen Rodríguez-Blázquez (Heliyon, 2023)
Aim: Societal ageing increases the need for correct and healthy ageing to ensure the well-being of older adults. Practical strategies are needed to acquire healthy habits for the ageing process. This study aims to analyse the lifestyle habits of subjects who are retired or close to retirement and identify factors that could influence their perceived health and that could be related to these habits. Methods: A Spanish observational, descriptive, cross-sectional study of subjects close to retirement-age. Socio-demographic, family, work, leisure, social, and clinical-psychological indicators were evaluated. Results: 1,700 participants (581 employed; 714 retirees; 405 other-status) were included, average age 63 years, 52% women. Most reported a satisfactory social life (90%), were in live-in relationships (74%), non-smoking (80%), followed a Mediterranean diet (73%), and took medicines daily (70%). Perceived health (EQ-VAS) was 75.9/100, with low disability (12-WHODAS) (7.4/100) and moderate/severe depression. Women reported higher disability (p < 0.001) and depression (p < 0.001), a better social life, and healthier lifestyle, but lower physical/work activity. Retirees reported less depression, better social life, healthier lifestyle, higher physical/work activity, and better sleeping habits. The multivariate model showed a significant association of health-status with disability level, number of chronic diseases, sleep habits, exercise, diet, and alcohol consumption. When depression level was introduced, age and being a woman were also related. Conclusions: Retirement does not mean worse health but rather an opportunity to reinforce favourable health activities and improve lifestyle factors. Incorporating the differences related to gender and employment status in health-perception will facilitate the design of healthy ageing strategies.